The Bourgeois ascendancy under Fatimids (Journal of the College of Education for Women, 2019)
The bourgeoisie groups derived great advantages from the system upon which the Fatimids built up their Regime out the land-tax and other taxes against a fixed sum . The surpulus revenue was the prophet of the farmers . A striking feature of the Fatimid was freedom of enterprise .All sectors of economic life were free-crafts , industry and trade . The government interfered in the trade in victuals only so far to in order to guarantee the supply of wheat to the big townsThe Egyptian Bourgeoisie enjoyed also the great prosperity which was produced among other reasons by the inflationary system of Fatimid economy .The maintenance of gold dinar being almost pure and of full weight was only possible because Egypt steadily received considerable quantities of gold from the western Sudan, which must have been a strong stimulus for an expanding economy , for the rise in the prices of various goods and for the settling of new enterprisesThe great shortage of pure silver dirhams which was felt during the Fatimid reign in Egypt , as in other Near-Eastern countries , did not check this trendAnother major in the remarkable buoyancy of Egypt’s economy in the Fatimid period and the enrichment of the bourgeoisie was the great development of its international trade.